2019
DOI: 10.1002/nafm.10324
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Dependent Retention of Pelagic‐Oriented Kokanee in Multimesh Gill Nets

Abstract: Recent studies evaluating the size selectivity of standard, horizontal, benthic gill nets for some common sport fish have demonstrated congruence across regions and gear configurations. Studies evaluating retention in gill nets designed to sample pelagic‐oriented fish (e.g., vertical and curtain nets) are rare, which has limited corresponding assessments of generality. This study estimated the retention of kokanee Oncorhynchus nerka (lacustrine Sockeye Salmon) in multimesh vertical gill nets using catch data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Various authors have suggested that accounting for selectivity will lead to more accurate estimates of population parameters [7,14,15,33]. Smith et al [7] suggested that data collected…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have suggested that accounting for selectivity will lead to more accurate estimates of population parameters [7,14,15,33]. Smith et al [7] suggested that data collected…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, managers may want to consider using larger mesh sizes or alternative size selectivity adjustments when monitoring kokanee populations that contain individuals larger than 440 mm. For instance, Hansen () extended size selectivity adjustments of kokanee up to 500 mm by incorporating a “tangling” parameter to account for fish whose girth exceeded that of the available mesh. Conversely, managers may wish to consider the applicability of fisheries‐dependent data for characterizing kokanee populations.…”
Section: Discussionmentioning
confidence: 99%
“…In fall 2020, a floating trap net called a Merwin trap (Hubert et al., 2012) was deployed nearshore and retrieved on 19 October and 26 October to collect mature kokanee salmon ( n = 146) in addition to those collected during the salmon run to Roaring Judy Hatchery. Finally, from 2018 to 2020, vertical gill nets, a standard suite of six multi‐mesh nets described in Hansen (2019), were deployed overnight in offshore regions of Blue Mesa Reservoir in the spring (May/June), summer (July/August) and fall (November) to collect both mature and immature kokanee salmon ( n = 580).…”
Section: Methodsmentioning
confidence: 99%